Pengaruh Model Pembelajaran Kooperatif Tipe Team Assisted Individualization dan Self-Efficacy terhadap Kemampuan Pemecahan Masalah Fisika Siswa di MTs N Kota Jambi - Intan Iklima; Jefri Marzal; Damris M. (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
Mathematical problem-solving skills in learning physics is important. According to the preliminary study conducted at MTsN Jambi, it is known that the mathematical problem solving ability of students in learning physics still low. This study aims to improve the mathematical problem solving capability by applying the team assisted individualization and self-efficacy cooperative learning model. This study was experimental research by using questionnaire self-efficacy instrument and essay test. The population of this study was seventh grade students MTsN Jambi. Data analysis was performed by using two ways-ANOVA and Tukey test. The results shows that: (1) cooperative learning model of TAI influences to students’ physical problem solving capability, (2) SE influences the students’  physical problem solving capability, (3) there are differences in high SE students’  physical problem solving capability by using cooperative learning model type TAI from those who using conventional learning models, (4) there are differences in low SE students’  physical problem solving capability by using cooperative learning model TAI type than those using conventional learning model, (5) there is no interaction between the cooperative learning model of TAI and SE of students in MTsN Jambi.